Les thermes maritimes de Baelo Claudia et le suburbium occidental - Darío Bernal-Casasola; José J. Díaz Rodríguez; José Á. Expósito Álvarez (Mélanges de la Casa de Velázquez)
This article summarises the data from several seasons of excavation at the south-western suburbium of Baelo Claudia, separated from the walled town by the Villas stream and abutting the sea front. These archaeological works have produced evidence of early occupation of the site from the 2nd century BCE up to contemporary times, albeit the site had its heyday between the 2nd and 3rd centuries CE, when baths of considerable size were built and in use. Several areas belonging to the different parts of the baths complex have been identified—particularly important is a natatio of considerable size—along with other functional areas always found in sites of this kind—a cistern and water redistribution tank. Various decorative elements for baths have also been identified, among them a marble copy of the Doryphoros of Polykleitos and a mosaic with a marine motif.